2000
DOI: 10.1128/aac.44.8.2118-2125.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in 23S rRNA and Ribosomal Protein L4 Account for Resistance in Pneumococcal Strains Selected In Vitro by Macrolide Passage

Abstract: The mechanisms responsible for macrolide resistance in Streptococcus pneumoniae mutants, selected from susceptible strains by serial passage in azithromycin, were investigated. These mutants were resistant to 14-and 15-membered macrolides, but resistance could not be explained by any clinically relevant resistance determinant [mef(A), erm(A), erm(B), erm(C), erm(TR), msr(A), mph(A), mph(B), mph(C), ere(A), ere(B)]. An investigation into the sequences of 23S rRNAs in the mutant and parental strains revealed ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
261
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(269 citation statements)
references
References 54 publications
(55 reference statements)
5
261
3
Order By: Relevance
“…In general, mechanisms underlying resistance against these antimicrobials are known to involve active efflux of the antibiotics and modification of the ribosomal target by enzymes such as rRNA methylase, enzymic inactivation or mutations in the 23S rRNA gene, as described previously in various organisms by Chisholm et al (2010), Li et al (2011) and Versalovic et al (1996). Another mechanism, involving point mutations in genes encoding the ribosomal proteins L4 (rplD) and L22 (rplV), has been reported in some clinical isolates (Matsuoka et al, 2004;Tait-Kamradt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In general, mechanisms underlying resistance against these antimicrobials are known to involve active efflux of the antibiotics and modification of the ribosomal target by enzymes such as rRNA methylase, enzymic inactivation or mutations in the 23S rRNA gene, as described previously in various organisms by Chisholm et al (2010), Li et al (2011) and Versalovic et al (1996). Another mechanism, involving point mutations in genes encoding the ribosomal proteins L4 (rplD) and L22 (rplV), has been reported in some clinical isolates (Matsuoka et al, 2004;Tait-Kamradt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Macrolide resistance in Streptococcus pneumoniae is due to either target site modification-generally depending on a posttranscriptional modification of 23S rRNA mediated by ermclass methylases (39) or less often on mutations in 23S rRNA or ribosomal proteins (7,37,38)-or active efflux. In this study, 120 erythromycin-resistant pneumococci were investigated for macrolide resistance phenotypes and genotypes, with emphasis on the discrimination between mef(A) and mef(E).…”
mentioning
confidence: 99%
“…It is noteworthy that, in mutans streptococci, mutations in the 23S rRNA and rplC genes were first identified in S. criceti strain OMZ 61. In S. pneumoniae, a single A2058G mutation was sufficient to cause elevation of erythromycin MICs, but macrolide resistance was conferred only when two or more alleles harbored an A2058G mutation (Tait-Kamradt et al, 2000). Direct sequencing analysis and sequence analysis of clones indicated that the A2059G mutation (A2058G in E. coli numbering) is predominant in alleles of strain OMZ 61.…”
Section: Discussionmentioning
confidence: 99%
“…DNA hybridization analysis of the 23S rRNA genes in S. criceti strains As mutations of the 23S rRNA genes and the rplD gene of S. pneumoniae are associated with resistance to macrolides (Tait-Kamradt et al, 2000;Wierzbowski et al, 2007), we first examined the 23S rRNA genes (rrl genes) of the four S. criceti strains by DNA hybridization. Genome sequence analysis of strain HS-6 T indicated that the genome contains five rrl genes and that five fragments, 12.8, 9.4, 9.2, 7.9 and 7.1 kb in size, should be detected after EcoRI digestion, whereas five fragments, 7.4, 6.0, 5.3, 3.8 and 3.3 kb in size, should be detected after EcoRI and BbsI double digestion (Richards Fig.…”
Section: Susceptibility Of S Criceti Strains To Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation